1998
DOI: 10.1038/sj.bjp.0702213
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent contractile actions of proteinase‐activated receptor‐2‐activating peptides in human umbilical vein: release of a contracting factor via a novel receptor

Abstract: 1 The contractile actions of the proteinase-activated receptor-2-activating peptides (PAR 2 APs), SLIGRL-NH 2 (SL-NH 2 ), SLIGKV-NH 2 (KV-NH 2 ), trans-cinnamoyl-LIGRLO-NH 2 (tc-NH 2 ), and the PAR 1 -AP, TFLLR-NH 2 (TF-NH 2 ) as well as trypsin and thrombin were studied in endotheliumdenuded and intact human umbilical vein (HUV) ring preparations. 2 In HUV rings with, but not without an intact endothelium, PAR 2 APs caused a concentrationdependent contractile response, whereas LSIGRL-NH 2 trypsin and PAR 1 AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…An endothelium-independent direct contractile e ect on the rabbit aorta (Komuro et al, 1997) and the endothelium-dependent contraction in the human umbilical vein (Saifeddine et al, 1998) were also reported. However, there has so far been no report on direct relaxation.…”
Section: British Journal Of Pharmacology Vol 134 (4)mentioning
confidence: 90%
“…An endothelium-independent direct contractile e ect on the rabbit aorta (Komuro et al, 1997) and the endothelium-dependent contraction in the human umbilical vein (Saifeddine et al, 1998) were also reported. However, there has so far been no report on direct relaxation.…”
Section: British Journal Of Pharmacology Vol 134 (4)mentioning
confidence: 90%
“…In support of the latter postulate, we observed an SLIGRL-NH 2 -induced afferent arteriolar vasoconstriction after NO synthase inhibition. Previous studies using other vascular preparations have demonstrated that SLIGRL-NH 2 elicits endothelium-dependent (30,32) and endothelium-independent (23) vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…PAR-2 is unique, in that it is activated by trypsin and mast cell-derived tryptase (8,26) but not by thrombin (26). PAR-2 can also be activated by a synthetic peptide corresponding to the enzymatically exposed ligand sequence SLIGRL or SLIGRL-NH 2 (26,(30)(31)(32) and is expressed in vascular and nonvascular smooth muscle (25,31) and in vascular endothelium (22).…”
mentioning
confidence: 99%
“…Thrombin is able to induce vasospasm 26,27 by activation of protease-activated receptors. 28,29 In fact, inhibition of thrombin with hirudin was shown to limit infarct size in a rabbit coronary ligation model. 30 Microvascular patency and consequently myocardial perfusion are predictors of mortality after thrombolytic therapy 31 and after C,D).…”
Section: Discussionmentioning
confidence: 99%